Comparing the case mix and survival of women receiving breast cancer care from one private provider with other London women with breast cancer: pilot data exchange and analyses. Issue 1 (December 2016) - Davies, Elizabeth; Coupland, Victoria; Dixon, Steve; Mokbel, Kefah; Jack, Ruth
Abstract Background Data from providers of private cancer care are not yet formally included in English cancer registration data. This study aimed to test the exchange of breast cancer data from one Hospital Corporation of America International (HCAI) hospital in London with the cancer registration system and assess the suitability of these data for comparative analyses of case mix and adjusted survival. Methods Data on 199 London women receiving 'only HCAI care', 278 women receiving 'some HCAI care' (HCAI and other services), and 31, 234 other London women diagnosed between 2005 and 2011 could be identified and compared. Overall survival was estimated using the Kaplan-Meier method, and Cox regression was used to adjust for age, socioeconomic deprivation, year of diagnosis, stage of disease and recorded treatment. Results Women receiving 'only HCAI care' were younger, lived in areas of higher affluence (47.8 % vs 27.6 %) and appeared less likely to be recorded as having screen-detected (2.5 % vs 25.0 %) disease than other London women. Women receiving 'some HCAI care' were more similar to 'HCAI only' women. Although HCAI stage of disease data completeness improved during the study period, this was less complete overall than cancer registration data and limited the comparative survival analyses. An apparent survival advantage for 'HCAI only' women compared with other London women (hazard ratio 0.48, 95 % confidence interval (CI): 0.32-0.74) was attenuated and no longer statistically significant after adjustment (0.79, 95 % CI: 0.51-1.21). Women receiving 'some HCAI care' appeared to have higher survival (hazard ratio 0.24, 95 % CI 0.14-0.41) which was attenuated to 0.48 (95 % CI: 0.28-0.80) in the fully adjusted model. Conclusions Exchange of data between the private cancer sector and the English cancer registration service can identify patients who receive all or some private care. The better survival of women receiving only or some HCAI breast cancer care appears to be at least partly explained by demographic, disease, and treatment factors. However, larger studies using similarly quality assured datasets and more complete staging data from the private sector are needed to produce definitive comparative results.